Long-term real-world outcomes of first-line immunotherapy in non-small cell lung cancer – a population-based cohort study in Sweden - Gunnar Wagenius; Anders Vikström; Anders Berglund; Stina Salomonsson; Goran Bencina; Xiaohan Hu; Diana Chirovsky; Hans Brunnström (Acta Oncologica)
Background: In a previous study, we explored real-world programmed death-ligand 1 (PD-L1) testing and treatment patterns for patients with advanced non-small cell lung cancer (NSCLC) in the era of immune-oncology. The present study aimed to investigate overall survival (OS) with PD-(L)1 inhibitors with longer-term follow-up in the Swedish setting.